Yellow Fever's Historical Lessons for COVID-19: International Interventions and Disease Control in Early Twentieth-century Ecuador and Guatemala. Issue 4 (December 2021) - Carey, David
Throughout tropical urban Latin America, yellow fever wreaked havoc. Located at sea level, Guayaquil (Ecuador) and Puerto Barrios (Guatemala) were particularly susceptible to yellow fever; yet, Ecuadorians and Guatemalans enjoyed significant success in early twentieth-century campaigns against yellow fever. Reflecting international efforts that informed, collaborated with, and at times underwrote Latin American public health campaigns, the Rockefeller Foundation (RF) sent representatives to Guatemala and Ecuador in the mid-1910s to eradicate yellow fever. While those interventions enjoyed immediate success, the long-term effects were more ambiguous. By collaborating with RF, Ecuador had all but eradicated yellow fever by 1919. In Guatemala, however, a few months after RF declared Guatemala free of yellow fever, influenza struck, likely originating from US military camps in Guatemala that RF sought to shield from yellow fever.  Analysis of early twentieth-century yellow fever epidemics and campaigns to arrest them sheds light on COVID-19 pandemic challenges. Even as knowledge of disease etiology was evolving in Ecuador and Guatemala, most leaders accepted or at least did not publicly reject scientific medicine. In contrast, beginning with the most powerful politicians and filtering down throughout federal, state, and municipal authorities, many US leaders rejected science crucial to the campaigns against COVID-19. Similarly, in a pattern that resonates with US residents rejecting precautionary measures against COVID-19 such as wearing masks and maintaining social distance, compliance with anti-yellow fever campaigns was not always forthcoming.